Attendance and non-attendance for breast screening at the south east London breast screening service. Issue 6691 (8th July 1989) - McEwen, J.; King, E.; Bickler, G.
Abstract : OBJECTIVES–To ascertain the reasons for a low rate of response for breast screening. DESIGN–All relevant aspects of the organisational process examined, including general practitioners' notes. Non-responders visited and interviewed. SETTING–An inner city breast screening service working on the model advocated by the Forrest report. SUBJECTS–288 Women aged 50-64 registered with several general practices and invited for screening by post. MAIN OUTCOME–Determination of factors important for success of breast screening programmes. RESULTS–After five women were excluded by their general practitioners the response rate was 129 out of 283 (46%), but 99 (35%) of the women did not receive their invitations because of inaccuracies in the family practitioner committee's database and general practitioners failing to check women's addresses completely. CONCLUSIONS–Increased rates of response will depend on enabling general practitioners to check addresses and on an increased awareness of the importance of information.